Kewajiban dan Karakteristik Belajar Mengajar Ala Rasulullah (Perspektif Hadis) - Asror, Fuad Mafatichul; Janah, Futihatul; Nafi'ah, Eriza Choirotin (Tawazun: Jurnal Pendidikan Islam, 2021)
Islam is a religion that requires its people to always seek knowledge, a Muslim is required to study from birth to the end of life. Educators in teaching their students are required to provide the best version of teaching. Educators in this case can imitate the learning that the Prophet has taught. This can be seen in the Qur'an and hadith. The type of research used in this research is library research. The results of this study are in the teaching and learning process, it should refer to the characteristics of the Prophet's teaching. Gentle towards students, nurturing, motivating, correlated an event in a learning process Familiarizing dialogue and mental strategies, keeping names secret when criticizing and giving appreciation to students. In order for education to make an impression on the hearts of students, students should apply the method of giving good uswatun hasanah to them. Abstrak Islam adalah agama yang menuntut uamtanya untuk selalu menuntut ilmu, seorang muslim diwajibkan menuntut ilmu dari lahir hingga akhir hayat. Pendidik dalam memberikan pengajaran kepada peserta didiknya dituntut untuk memberikan pengajaran dalam versi terbaiknya. Pendidik dalam hal ini dapat meneladani pembelajaran yang telah Rasulullah ajarkan. Hal tersebut dapat dilihat pada Al-Qur'an maupun hadis. Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian kepustakaan (library research) hasil penelitian ini adalah dalam proses belajar mengajar seyogyanya mengacu pada karakteristik mengajar ala Rasulullah. Lemah lembut terhadap peserta didik, mengayomi, memberi motivasi, mengkorelasikan suatu peristiwa dalam suatu proses pembelajaran Membiasakan strategi dialog dan mental, merahasiakan nama ketika mengkritik dan memberikan apresiasi kepada peserta didik. Agar pendidikan membekas pada hati peserta